1985
DOI: 10.1029/jb090is01p00123
|View full text |Cite
|
Sign up to set email alerts
|

The Leoville (CV3) accretionary breccia

Abstract: Leoville is a CV3 chondrite that contains a large variety of inclusions Besides refractory inclusions resembling those in Allende, fine‐grained, dark inclusions are especially prominent. Same of these are xenoliths of material very similar to CM chondrites in texture, bulk composition, and oxygen isotopes, However, they show an unusually large range in the degree of hydrous alteration. Other dark inclusions are similar to host matrix. The CV3 host of this breccia is similar to other CV chondrites, although les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…High-Co, low-Ni metal grains (up to 39 wt% Co) have been found in equilibrated LL chondrites (Afiattalab and Wasson 1980;Rubin 1990). Such occurrences have also been observed in a few unequilibrated chondrites: in Colony CO3 , in two xenoliths in Leoville CV3 (Kracher et al 1985), in the ungrouped carbonaceous chondrite Ningqiang (Hua et al 1995), and in Y-74660 LL3.0 (Kimura 2000). In Krymka, many analyses of metal grains in different samples did not bring in Co content values higher than 2 wt% in kamacite and 1.5 wt% in tetrataenite (Rambaldi and Wasson 1984;Perron and Bourot-Denise 1992 and unpublished), except for one kamacite grain and one tetrataenite grain with 2.7 and 2 wt% Co, respectively (Semenenko et al 1987).…”
Section: High-co Metal Grainsmentioning
confidence: 97%
“…High-Co, low-Ni metal grains (up to 39 wt% Co) have been found in equilibrated LL chondrites (Afiattalab and Wasson 1980;Rubin 1990). Such occurrences have also been observed in a few unequilibrated chondrites: in Colony CO3 , in two xenoliths in Leoville CV3 (Kracher et al 1985), in the ungrouped carbonaceous chondrite Ningqiang (Hua et al 1995), and in Y-74660 LL3.0 (Kimura 2000). In Krymka, many analyses of metal grains in different samples did not bring in Co content values higher than 2 wt% in kamacite and 1.5 wt% in tetrataenite (Rambaldi and Wasson 1984;Perron and Bourot-Denise 1992 and unpublished), except for one kamacite grain and one tetrataenite grain with 2.7 and 2 wt% Co, respectively (Semenenko et al 1987).…”
Section: High-co Metal Grainsmentioning
confidence: 97%
“…Some CM clasts similar to PV3 apparently arrived at velocities high enough to be shocked and dehydrated but not high enough to be vaporized. In general, dark carbonaceous chondrite-like clasts in other meteorite classes (e.g., CV3 chondrites; Kracher et al 1985; see references in Wasson and Wetherill 1979) are a poor match to known CM meteorites. It is unclear whether a selection bias exists.…”
Section: Cm-like Clasts In the Asteroid Population And The Inner Solamentioning
confidence: 99%
“…Leoville consists of two individual stones; the first, weighing 1.629 kg, was recovered prior to 1965 and the second 6.5 kg stone was recovered in 1966 (Kracher et al 1985). Leoville has experienced a higher degree of terrestrial weathering than Vigarano, as it was found buried in the soil (Kracher et al 1985), indicating that it had an extended residence time in a subsurface environment. At least one calcite occurrence has been reported in the literatures (Sylvester et al 1993).…”
Section: Leovillementioning
confidence: 99%